Boundary Crossers: How Providers Facilitate Ethnic Minority Families' Access to Dementia Services. (29th April 2021) - Brijnath, Bianca; Gilbert, Andrew S; Antoniades, Josefine; Croy, Samantha; Kent, Mike; Ellis, Katie; Browning, Colette; Goeman, Dianne; Adams, Jon
Abstract: Objectives: Providers who work closely with ethnic minority people with dementia and their families are pivotal in helping them access services. However, few studies have examined how these providers actually do this work. Using the concept of "boundary crossers, " this article investigates the strategies applied by these providers to facilitate access to dementia services for ethnic minority people with dementia and their families. Methods: Between 2017 and 2020, in-depth video-recorded interviews were conducted with 27 health, aged care, and community service providers working with ethnic minority people living with dementia across Australia. Interviews were conducted in one of seven languages and/or in English, then translated and transcribed verbatim into English. The data were analyzed thematically. Results: Family and community stigma associated with dementia and extra-familial care were significant barriers to families engaging with services. To overcome these barriers, participants worked at the boundaries of culture and dementia, community and systems, strategically using English and other vernaculars, clinical and cultural terminology, building trust and rapport, and assisting with service navigation to improve access. Concurrently, they were cognizant of familial boundaries and were careful to provide services that were culturally appropriate without supplanting the families' role. Discussion: In negotiating cultural, social, and professional boundaries, providers undertake multidimensional and complex work that involves education, advocacy, negotiation, navigation, creativity, and emotional engagement. This work is largely undervalued but offers a model of care that facilitates social and community development as well as service integration across health, aged care, and social services.